2017
DOI: 10.1177/0018720817715360
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Affective and Cognitive Restoration: Examining the Restorative Effects of Casual Video Game Play

Abstract: Many activities in life require sustained cognitive demand, which are stressful and decrease performance, especially for workers in performance-critical domains. Our research suggests some leisure activities are better than others for restoring fatigued affective processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
(46 reference statements)
3
19
0
Order By: Relevance
“…Most studies used a randomized-controlled research design 16,19,[22][23][24] to investigate the effects of CVGs on anxiety, depression, stress, or mood symptoms. Fish et al 25 employed a quasi-experimental design with participants who had been diagnosed with clinical depression.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies used a randomized-controlled research design 16,19,[22][23][24] to investigate the effects of CVGs on anxiety, depression, stress, or mood symptoms. Fish et al 25 employed a quasi-experimental design with participants who had been diagnosed with clinical depression.…”
Section: Methodsmentioning
confidence: 99%
“…All studies that examined mood and stress noted significant improvements when compared with a passive break, surfing the web, or a relaxation activity. 16,27,32 Both studies that examined the effects of a CVG for reducing depressive symptoms found improvements in their outcome variables. 26,28…”
Section: Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is supported by studies that show that the use of video games helps decrease stress in work environments. [41]…”
Section: Pre-nursing School Copingmentioning
confidence: 99%
“…14 In addition to long-term decrements in physical health, more immediate impact occurs on job performance, 15 some of these via cognitive effects. 16 Consequently, offering strategies to reduce workplace stressors and/or help anesthesia providers maintain effective performance when under stress is an important area for patient safety. An obese patient's oxygen saturation (sat) falls slowly to 90% during robotic prostatectomy in steep Trendelenburg position.…”
Section: Stressmentioning
confidence: 99%